Perancangan Tempat Sampah Pintar Menggunakan Sensor Ultrasonik Berbasis Mikrokontroler Arduino - Nanang Endriatno (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2022)
The application of technology by modifying mechanical devices into automatic tools is one approach to facilitate human work so that it can work effectively and efficiently. The application can be applied to the trash by applying electronic technology that allows the device to open and close automatically. The purpose of this research is to make a smart trash can. The method developed in the trash can is to use a microcontroller, ultrasonic sensor, servo motor, and a drive mechanism to open the garbage cover automatically, making it easier when disposing of garbage. Based on the tests carried out, it can be concluded that the design of the trash can using ultrasonic sensors, servo motors based on the Arduino microcontroller, and the mechanical drive system can produce the required output according to the design. The ultrasonic sensor and its mechanical system can function very well according to the plan. The test method shows that there is no difference between the programmed sensor reading distance and the sensor reading distance, with a minimum and maximum sensor distance of 10-60 cm. The programming and mechanical system for opening the garbage cover can be designed with an opening angle of 5°-65° and an opening speed of 0.28-1.23 s with a variation of the closing holding time of 1-5 s, indicating that the servo motor and its mechanical system can function properly. according to the program created.